The Effect of Main Bronchus Stump Closure Method on the Incidence of Stump Failure during Pneumonectomy for Tuberculosis - Giller, D. B.; Basangova, V. A.; Popova, A. A.; Saenko, S. S.; Martel, I. I. (Tuberkulëz i bolezni lëgkikh, 2024)
The objective: to evaluate the effectiveness of various methods for the main bronchus stump closure when performing pneumonectomy for destructive pulmonary tuberculosis. Subjects and Methods. Treatment results of 1211 tuberculosis patients from 1958 to 2022 were studied. The patients were treated in three clinical phthisiopulmonary centers. All of them underwent pneumonectomy with closure of the main bronchus stump by different methods. Results. We studied results of using different methods for suturing the main bronchus during pneumonectomy. For this purpose, the incidence of early fistulae of the bronchial stump and mortality from bronchopleural complications were assessed. The worst result was observed when using a mechanical suture (21.7% and 8.3%, respectively), the combination of polyspast-circular ligature with mechanical suture improved the effectiveness (2.3% and 4.6%, respectively), and the best result was demonstrated by the stump-free method of bronchus closure offered by D.B. Giller et al. (0.3% and 0.1%, respectively).